Elasto-Plastic Behavior of Aluminum Foams Subjected to Compression Loading - Silva, H.M.; Carvalho, C.D.; Peixinho, N.R. (Прикладная механика, 2017)
The non-linear behavior of uniform-size cellular foams made of aluminum is investigated when subjected to compressive loads while comparing numerical results obtained in the Finite Element Method software (FEM) ANSYS workbench and ANSYS Mechanical APDL (ANSYS Parametric Design Language). The numerical model is built on AUTODESK INVENTOR, being imported into ANSYS and solved by the Newton – Raphson iterative method. The most similar conditions were used in ANSYS mechanical and ANSYS workbench, as possible. The obtained numerical results and the differences between the two programs are presented and discussed. Досліджено нелінійну поведінку однорідних кліткоподібних пін, зроблених з алюмінію і підданих стиску. Порівнено числові результати, одержані двома програмними пакетами: Finite Element Method software (FEM) ANSYS workbench і ANSYS Mechanical APDL (ANSYS Parametric Design Language). Числову модель побудовано в AUTODESK INVENTOR і надалі її імпортовано в ANSYS і розв'язано за допомогою методу Ньютона - Рафсона. Використано якомога ближчі умови у вказаних пакетах. Представлено і прокоментовано одержані числові результати і спостережені відмінності між двома пакетами.